Mapping the research landscape of microRNAs in pain: a comprehensive bibliometric analysis - Wang, Huaiming; Li, Qin; Zou, Jiang; Shu, Jinjun; Zhang, Aimin; Zhang, Hongwei; Zhao, Qi; Liu, Shunxin; Chen, Chan; Chen, Guo (Frontiers in Molecular Neuroscience, 2024)
Background and objectivesMicroRNAs (miRNAs) have demonstrated significant potential in pain medicine research, including mechanisms, diagnosis, and therapy. However, no relative bibliometric analysis has been performed to summarize the progress in this area quantitatively.MethodsLiterature was retrieved from the Web of Science Core Collection online database. A total of 1,295 papers were retrieved between January 1, 2000 and September 21, 2023 and underwent visualization and analysis using R software [Library [bibliometrix] and biblioshiny packages], VOSviewer (version 1.6.18), CiteSpace software (version 6.2.R4), and the bibliometrics website (http://bibliometric.com).ResultsPublications in this field have increased annually since 2000, demonstrating growing research interest. China emerged as the most productive country, followed by the United States and Germany. Keyword analysis identified “expression,” “neuropathic pain,” and “microRNAs” as the most relevant keywords. Extensive collaboration among countries and institutions was also observed.ConclusionThe bibliometric analysis revealed a rapid growth of publications related to miRNAs and pain in the past 2 decades. Keywords analysis indicates that “expression,” “neuropathic pain,” and “microRNA” are the most frequently used words in this research field. However, more robust and globally recognized basic studies and clinical trials from prestigious journals are required.